Eve of the Emperor penguin - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2008)
The magic tree house takes Jack and Annie to Antarctica to search for the fourth secret of happiness for Merlin.
Keywords: Tree houses -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Antarctica -- Juvenile fiction